Condensation of nucleic acids by intercalating aromatic cations. - Kapuscinski, J (1984)
Certain intercalating aromatic cations, such as the fluorochrome acridine orange or the antitumor drug Mitoxantrone, induce condensation of nucleic acids in solutions. The appearance of the condensed form during titration of nucleic acids with these intercalating ligands can be quantitatively monitored by light scatter measurements. The resulting highly reproducible light scatter transition curves are typical of the cooperative processes, and the transitions occur at different critical concentrations of the ligands depending upon both the ligand itself and the primary structure (base and sugar composition) and the secondary structure (single- or double-stranded) of the nucleic acids. The mechanism of condensation of nucleic acids by intercalating cationic ligands is discussed in light of the model of interactions occurring between certain intercalators and single-stranded nucleic acids and compared with the condensation induced by polyvalent "simple" cations such as Co3+ or spermine4+. The described phenomenon can have an application in analytical and preparative biochemistry for characterization of the primary and secondary structure of nucleic acids and for separation of the compounds. The possibility that the condensation plays a role in mutagenic and pharmacological effects of aromatic cations is considered.